The United States government’s Caribbean Basin Initiative - Wilfred Whittingham (CEPAL Review, 1989)
The objective of the paper is to provide a better understanding of the CBI Programme and examine its achievements in the light of the objectives and expectations. To put the discussion in perspective, a brief economic and sociopolitical background is given, followed by a statement of the programme’s objectives and a brief description of its main plans; legislation, administrative action and technical assistance. Data on foreign trade, direct investment and development assistance point to the conclusion that most of the indicators have declined. Despite a higher level of official financial aid since the programme started in 1984, the overall achievement has been negligible. Some countries have fared better than others and there are some signs of increasing diversification of exports and better performance of newer exports than of traditionals.